1995
DOI: 10.1177/00220345950740090701
|View full text |Cite
|
Sign up to set email alerts
|

EP-GP and the Lipocalin VEGh, Two Different Human Salivary 20-kDa Proteins

Abstract: Two salivary 20-kDa proteins [the human lipocalin Von Ebner's gland protein (VEGh) and extraparotid glycoprotein (EP-GP)] show several remarkable similarities and differences. The latter is identical to secretory actin-binding protein (SABP), gross cystic disease fluid protein-15 (GCDFP-15), prolactin-induced protein (PIP), and 17-kDA CD4-binding glycoprotein (gp17). Much is known about the distribution, localization, biochemical characteristics, and molecular biology of these two proteins, yet there are only … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

1996
1996
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 47 publications
0
11
0
Order By: Relevance
“…The r‐gp17/GCDFP‐15 dimers were stable when stored at −80 °C, but gave rise to a form of about 70 kDa in about three weeks when stored at 4 °C, as reported for EP‐GP [19]. To determine whether gp17/GCDFP‐15 was also present as the dimeric form in HSP, samples were submitted to anion‐exchange chromatography (Q‐Fast Flow) before gel filtration onto a Superdex 200 column.…”
Section: Resultsmentioning
confidence: 92%
“…The r‐gp17/GCDFP‐15 dimers were stable when stored at −80 °C, but gave rise to a form of about 70 kDa in about three weeks when stored at 4 °C, as reported for EP‐GP [19]. To determine whether gp17/GCDFP‐15 was also present as the dimeric form in HSP, samples were submitted to anion‐exchange chromatography (Q‐Fast Flow) before gel filtration onto a Superdex 200 column.…”
Section: Resultsmentioning
confidence: 92%
“…EP‐GP is another example of a protein that originally had been implicated in the formation of the dental pellicle, because of its high affinity for hydroxyapatite (Rathman et al , 1989). Later studies demonstrated that EP‐GP protein is present in several excretory body fluids, including sweat, semen and tears, and is identical to secretory actin binding protein (SABP) and Gross Cystic Disease Fluid Protein (GCDFP‐15) (Schenkels et al , 1994, Schenkels, Veerman and Nieuw Amerongen, 1995a, 1995b; Caputo et al , 1999). The ubiquitous presence in mucosal secretions pointed to a more general protective role for EP‐GP, a concept that was supported by the observation that this protein binds to microorganisms (Schenkels et al , 1997) as well as to the CD4 receptor on monocytes (Autiero et al , 1997; Gaubin et al , 1999).…”
Section: Von Ebner Glands Protein (Vegh) and Secretory Leucocyte Protmentioning
confidence: 99%
“…Vol. 66,2009 Review Article tract, ear canal and skin [71], resulting in the inhibition of bacterial growth [24]. Its predominance in mucosaltype tissues, as well as its presence in saliva, tears, submucosal glands of the bronchi and apocrine glands of the skin, suggests that PIP may play an important role in mucosal immunity [24].…”
Section: Inhibition Of Bacterial Growthmentioning
confidence: 99%